Imam Syafi’i Dan Syairnya Lan Tanal Al- ‘Ilma Illa Bi Sittah (Kajian Analisis Unsur – Unsur Sastra) - Wahid, Nurcahyani; Hamsa, Hamsa; Fauziah, St. (Al-Syamail: Jurnal Bahasa dan Sastra Arab, 2024)
Poetry has been an integral part of literary heritage since ancient times. Over time, the objectives of poetry have expanded, covering various themes. This research focuses on the work of Imam Syafi’I, a renowned poet known for his poems during the Abbasid era. The study specifically delves into one of Imam al-Syafi’I’s poems that discusses knowledge, titled “Lantanᾱl al-‘Ilma Illa Bisittah.” The research methodology employed is a literature review, encompassing the search, collection, and analysis of data sources such as books and theses. The qualitative descriptive data used in the research involve the selection, analysis, and classification of poetic elements related to Imam Syafi’I’s poems. The findings reveal that Imam Syafi’I’s poem “Lantanᾱl al-‘Ilma Illa Bisittah” contains elements of ‘Ātifah (emotion), evident in verse “أخــي لــنْ تـــنالَ العـــلـمَ إلاَّ بــتَّةِ” which employs poetic language to evoke emotion and enhance the emotional appeal for the reader. Al-Fikrah (Idea) is present in verses such as ‘’ ذكاءٌ، وحِــــرْصٌ، واجتــهـادٌ، درهم، وصُحــبة وأستــــــــــــاذِ، طـول زمـان” demonstrating a dimension of thought in conveying literary messages, considered a distinctive feature of al-fikrah. Sūrah (Form/Language Style) plays a crucial role in shaping the poem’s essence, focusing on knowledge and enriching the meaning of the poem, allowing for easier identification and enjoyment of its literary elements. However, the element of al-khᾱyal (imagination) is not present in Imam al-Syᾱfi’I’s poem, as it lacks imaginative content. The research identifies the absence of al-khᾱyal as a distinctive feature of the poem “Lantanᾱl al-‘Ilma Illa Bisittah.”